Introduction of a quality improvement curriculum in the Department of Internal Medicine, Lincoln Medical Center. Issue 1 (2nd January 2017) - Venugopal, Usha; Kasubhai, Moiz; Paruchuri, Vikram
ABSTRACT: Community hospitals with limited resources struggle to engage physicians in Quality improvement initiatives. We introduced Quality Improvement (QI) curriculum for residents in response to ACGME requirements and surveyed the residents understanding of QI and their involvement in QI projects before and after the introduction of the curriculum. The current article describes our experiences with the process, the challenges and possible solutions to have a successful resident led QI initiative in a community hospital. Methods: A formal QI curriculum was introduced in the Department of Internal Medicine from September to October 2015 using the Model for Improvement from Institute for Health care Improvement (IHI). Learners were expected to read the online modules, discuss in small group sessions and later encouraged to draft their QI projects using the Charter form and PDSA form available on the HI website. Online surveys were conducted a week prior and 3 months after completion of the curriculum Results: 80% (100/117) of residents completed the pre-curriculum survey and 52% (61/117) completed the survey post curriculum. 96.7% of residents report that physicians should lead QI projects and training rather than the hospital administrators. Residents had 20% increase in understanding and confidence in leading quality improvement projects post curriculum once initiated. Most Residents (72%) feel QI should be taught during residency. Active involvement of residents with interest was seen after the initiation of Open School Institute of health improvement (IHI) curriculum as compared to Institutional led QI's. The resident interventions, pitfalls with change processes with an example of PDSA cycle are discussed. Conclusion: A Dedicated QI curriculum is necessary to prepare the physicians deliver quality care in an increasing complex health care delivery system. The strength of the curriculum is the ease of understanding the material, easily available to all, and can be easily replicated in a Community Hospital program with limited resources. Participation in QI by residents may promote constructive competitiveness among related hospitals in public system to improve delivery of safe care. Abbreviations: ACGME: Accreditation Council for Graduate Medical Education; IHI: Institute of Healthcare Improvement; PDSA: Plan-Do-Study-Act; PGY: QI: Quality improvement